Strategi Pengembangan Minuman Serbuk Herbal (Studi Kasus pada Usaha Minuman Serbuk “Erma” di Kota Pontianak) - Kurniati, Dewi; Kurniawan, Renaldi; Aritonang, Marisi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
The study aims to determine the right method for the development of  “Erma” powder herbal drink business in Pontianak City. Methods of the variables by analyzing using SWOT and SWOT matrix analysis. The results of study shows that alternative strategy for business development is to maintain product quality to improve marketing, expand product marketing innovation through social media sales, increase the quality and of production. Based on the SWOT analysis of the business position in quadrant I. The strategies that need to be implemented are; support an aggressive strategy, the strength possesses by taking advantage of existing opportunities leads to profit.